1994
DOI: 10.1042/cs0860703
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Endothelin-1-Like Immunoreactivity in Young Male Patients with Testicular Cancer Treated by CIS-Platinum: Comparison with other Urinary Parameters

Abstract: 1. Urinary excretion of endothelin-1-like immunoreactivity and urinary excretion of other parameters (beta 2-microglobulin, N-acetyl-beta-D-glucosaminidase and microalbumin) were measured before, within 1 week after and 2 weeks after the administration of cis-platinum in five young male patients with testicular cancer (mean age 33.0 years) and were compared. 2. Urinary endothelin-1-like immunoreactivity/creatinine during, 1 week after, and 2 weeks after cis-platinum treatment was significantly higher than befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…21 Since urinary albumin excretion is also an indicator of glomerular injury, very large and/or delayed increases in urinary albumin may reflect more extensive damage to the entire nephron. 23,24,28 Nonetheless, the current data largely support maximal increases in urinary albumin concentrations within 4 to 10 days after cisplatin infusion in patients with clinical and subclinical AKI (Table 1).…”
Section: Albuminsupporting
confidence: 59%
See 3 more Smart Citations
“…21 Since urinary albumin excretion is also an indicator of glomerular injury, very large and/or delayed increases in urinary albumin may reflect more extensive damage to the entire nephron. 23,24,28 Nonetheless, the current data largely support maximal increases in urinary albumin concentrations within 4 to 10 days after cisplatin infusion in patients with clinical and subclinical AKI (Table 1).…”
Section: Albuminsupporting
confidence: 59%
“…41 Furthermore, another report suggested that urinary NAG concentrations may return to baseline as early as 2 weeks after cisplatin treatment. 23 Interestingly, there was no evidence of an increase in baseline NAG levels after additional courses of cisplatin treatment (up to 6). 22,32,34 NAG, similar to B2M, did not correlate with accumulated cisplatin dose.…”
Section: Beta-2-microglobulinmentioning
confidence: 91%
See 2 more Smart Citations
“…Endothelin-1 is a 21-amino acid protein that possesses a vasoconstrictor effect; in the kidneys, it is expressed in mesangial cells and collecting ducts. Takeda et al [ 79 ] measured urinary endothelin-1-like immunoreactivity/Cr before and 1 and 2 weeks after cisplatin treatment; these authors reported that urinary endothelin-1-like immunoreactivity/Cr was significantly increased at 1 and 2 weeks after cisplatin treatment compared to pretreatment levels. Following cisplatin treatment, β2 microglobulin/Cr and endothelin-1-like immunoreactivity/Cr peaked on day 2 and subsequently declined, whereas NAG/Cr peaked on day 6.…”
Section: Biomarkers For Which Measurement Is Not Covered By Healthmentioning
confidence: 99%